Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1038/sj.npp.1300151
|View full text |Cite
|
Sign up to set email alerts
|

The Muscarinic M1/M4 Receptor Agonist Xanomeline Exhibits Antipsychotic-Like Activity in Cebus apella Monkeys

Abstract: Xanomeline is a muscarinic M 1 /M 4 preferring receptor agonist with little or no affinity for dopamine receptors. The compound reduces psychotic-like symptoms in patients with Alzheimer's disease and exhibits an antipsychotic-like profile in rodents without inducing extrapyramidal side effects (EPS) at therapeutically relevant doses. In the present study, we examined whether the xanomeline-induced functional dopamine antagonism found in rodent studies could also be observed in nonhuman primates. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 46 publications
3
56
1
Order By: Relevance
“…[140][141][142] Similar to traditional antipsychotic compounds, treatment with xanomeline inhibited the behavioral and motor effects of amphetamine and apomorphine in monkeys. 143 Recent data suggest that xanomeline is also an antagonist at the M 5 receptor. 144 As muscarinic neurons carrying M 5 receptors have synaptic contact with dopaminergic neurons in the brainstem, the functional antagonism of xanomeline at M 5 receptors may offer an additional modulatory pathway on dopaminergic cell-firing.…”
Section: Use Of Cholinesterase Inhibitors In Schizophreniamentioning
confidence: 99%
“…[140][141][142] Similar to traditional antipsychotic compounds, treatment with xanomeline inhibited the behavioral and motor effects of amphetamine and apomorphine in monkeys. 143 Recent data suggest that xanomeline is also an antagonist at the M 5 receptor. 144 As muscarinic neurons carrying M 5 receptors have synaptic contact with dopaminergic neurons in the brainstem, the functional antagonism of xanomeline at M 5 receptors may offer an additional modulatory pathway on dopaminergic cell-firing.…”
Section: Use Of Cholinesterase Inhibitors In Schizophreniamentioning
confidence: 99%
“…Although encouraging, there have been only two clinical studies with xanomeline published to date indicating that these initial findings should be viewed with caution until further clinical validation is reported. Xanomeline also showed robust efficacy in animal models predictive of APDlike activity comparable to the effects observed with the atypical antipsychotic clozapine, including reversal of psychostimulant-induced hyperlocomotion and disruption of prepulse inhibition (PPI) of the acoustic startle reflex (Andersen et al, 2003;Jones et al, 2005;Perry et al, 2001;Shannon et al, 2000;Stanhope et al, 2001). Unfortunately, xanomeline like other muscarinic agonists ultimately failed in clinical development due to a lack of complete receptor subtype selectivity resulting in adverse side effects associated with non-selective activation of peripheral M 2 and M 3 mAChRs (Bodick et al, 1997;Shekhar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, original clinical trials revealed frequent peripheral side effects that were not consistent with M 1 selectivity and led to interruption of testing (Mirza et al, 2003). More recent behavioral studies in rodents, primates, and clinical studies have pointed to potential profitable antipsychotic effects that are ascribed to the M 1 /M 4 agonistic profile of the drug (Bymaster et al, 2002;Andersen et al, 2003).…”
mentioning
confidence: 99%